L’écologie déséquilibrante de l’oubli chez Homo Numericus - Sung do Kim (Netcom)
The aim of this paper is to construct the problematics of the just balance between the memory and the forgetting in the digital era, which is in danger with the coming of the digital technology which memorizes everything while never forget. In the first part, we provide some elements of anthropology and epistemology on the relationships of co-determination between the Man and the technique. In the second part we underline that the digital memory could provoke a crisis of individual and collective identity. In this regard the issue of the right to be forgotten is evoked.